Identifying Disruptive Technologies in IT Industry - Rouhani Zeidanloo, Hossein; Špaček, Miroslav, 1954-; Vacík, Emil; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
In the dynamic realm of the IT industry, accurately assessing a company’s potential to disrupt or be disrupted is crucial for maintaining a competitive advantage. However, there is currently a lack of a comprehensive methodology that enables the anticipation of disruptive innovation (DI) within this sector. This research addresses this gap by introducing an innovative framework designed to evaluate the disruptive potential of IT companies in relation to one another. Unlike traditional models that primarily focus on predicting disruptive technologies, this framework adopts a multi-dimensional approach to analyze how companies might impact each other through innovation, incorporating factors such as business model innovation, customer demand, network effects and technological advancement. The primary objective of this dissertation is to propose a framework for the timely identification of disruptive innovations, providing a holistic tool that integrates a strong theoretical foundation with practical application. The framework was developed through an extensive review of existing models predicting technological disruptions and was further refined using qualitative research, including in-depth interviews with a diverse range of IT professionals, such as managers, engineers, product managers, CTOs, consultants, and marketing managers. These conversations provided valuable insights into the practical realities of the IT sector, ensuring the framework encompasses a wide range of perspectives across technical, managerial, and strategic dimensions.
The effectiveness of the framework was validated through three key case studies: a historical analysis of Apple’s disruption of Nokia, which underscored the transformative power of innovative business models and technological adoption; a contemporary examination of the competitive dynamics between Mondoo and Lacework, where the framework accurately predicted Mondoo’s inability to disrupt Lacework, later validated by Fortinet’s acquisition of Lacework; and an analysis of Mondoo vs. WIZ, where the framework correctly assessed Mondoo’s limitations in challenging WIZ, highlighted by Google’s offer to acquire WIZ for $23 billion, which was subsequently rejected. These case studies collectively demonstrate the framework’s robustness, applicability, and relevance in evaluating disruptive potential within both historical and current contexts. A significant component of the research involved applying the framework dynamically within a Silicon Valley startup specializing in cybersecurity, an area currently experiencing substantial disruption. This real-time application, incorporating current market data and trends, was essential in evaluating the framework’s relevance and reliability, with results indicating a high degree of accuracy in assessing the disruptive potential among IT companies. The outcomes confirmed the framework’s utility, with an observed reliability of 80%, making it a valuable tool for businesses strategizing in an ever-changing technological domain. This research contributes a practical tool adapted to the unique characteristics of the IT sector, offering strategic insights for IT professionals, strategists, and policymakers to navigate and leverage disruption opportunities effectively. Beyond academic discussion, the framework provides actionable guidance for identifying and addressing potential disruptions in the IT landscape.
Vedoucí práce: Miroslav Špaček
Závěrečná práce - Institut celoživotního vzdělávání (DBA)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet